KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DI SMA PELITA RAYA KUBU RAYA - Desy Anggreni; Usman Radiana; Wahyudi Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to knowing the Principal's Visionary Leadership in Improving the Quality of Education at Pelita Raya High School. The research method used is descriptive with a qualitative form. There were 8 participants, namely the Principal, Deputy Principal for Curriculum, Deputy Principal for Student Affairs, TU Staff, and Teachers. Data collection methods used interviews, documentation, and observation. Data analysis is done by reducing the data, namely summarizing the raw data, choosing the main things and focusing on the important things. The results of his research: 1) the visionary leadership role of school principals who focus on the future in improving the quality of education. 2) The visionary leadership of the principal as an agent of change in improving the quality of education is carried out by making plans for school activities through programs according to the development of science and technology, focusing on the vision and mission, building relationships both internally and externally, and taking advantage of opportunities; 3) The visionary leadership of the principal as a determinant of direction in improving the quality of education by understanding priorities, communicating and directing the vision and mission, determining school policies by focusing on teacher and student competencies; 4) The visionary leadership of school principals as professional trainers in improving the quality of education by empowering the academic community and providing examples, guiding, and moving them. In conclusion, the visionary leadership of the principal brought his institution to improve the quality of the school much better.